Innovative working time policy in the service sector: Responses to working time policy challenges by service sector unions - Roland Schneider (Hans-Böckler-Stiftung, 2018)
The aim of the study is to examine how trade unions in the service sector in selected EU countries respond to new work-related challenges. In particular, those countries were considered where working time standards are mainly regulated by collective agreements. The starting points of the study are the dissolution of a formerly stable and regular distribution of working time through flexibly organised and increasingly atypical working hours and the discrepancies between desired working times of employees and their working time reality, which are expressed in the polarisation of working time between women and men and between different qualification groups, in the blurring of gainful employment and time off and in problems of reconciling work and family life. The study is based not only on the evaluation of a written survey of member unions of UNI Europa, the European trade union federation of service unions, but also on the analysis of selected collective agreements. The focus in terms of content will be on new and innovative regulations for the reorganisation and distribution of working time, on a life-phase-oriented, gender- and age-compliant work-promoting design of working time and the promotion of further training and lifelong learning through collective bargaining and working time policy. The documented and analysed collective agreements can be considered as organisational and social innovations. They offer many employees the choice between an increase in income or an increase in time off, and they promote a balance between work and family time requirements. In addition, they enable new qualifications to be acquired under learningfriendly time structures. Thus, they not only form the basis for a redesign and redistribution of working time. They also improve the chances of a life-phase-oriented design of working time; this is especially true with regard to age-compliant work, but less so with regard to a fair distribution of working time between the sexes. It was not possible to perform an adequate examination in terms of whether and how newer working time options are used by employees, whether they help to reduce existing companyrelated inequalities regarding the realisation of individual time preferences, and which factors and conditions promote or inhibit these. Many of the working time arrangements discussed are still in the first phase of their implementation. However, the results of the study show that the gap between the programmatic demands for a modern and sustainable working time policy and the workplace-related organisation and design of working time has narrowed in many sectors and companies. Further reducing this gap is a high priority for many trade unions. On the one hand, they are concerned with strengthening compliance with legal and collective working time standards and reducing the gap between actual and agreed working hours. On the other hand, they are concerned with strengthening the working time sovereignty of employees in gainful employment. They expect that union collective bargaining and working time policies will help them to have work arrangements that will give them security and reliability, distribute working time more equitably and enable them to better reconcile work life and private life.
urn:nbn:de:101:1-2018102414531896365767
Keywords: 330